2020
DOI: 10.1111/codi.15276
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing omentoplasty for management of chronic pelvic sepsis by intra‐operative fluorescence angiography: a comparative cohort study

Abstract: Aim Pelviperineal wound complications frequently occur after salvage surgery for chronic pelvic sepsis despite using an omentoplasty. Sufficient perfusion of the omentoplasty following mobilization is essential for proper healing. This study investigated the impact on short-term clinical outcomes of fluorescence angiography (FA) using indocyanine green for assessment of omental perfusion in patients undergoing salvage surgery. Method This was a comparative cohort study including consecutive patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Remarkably, ICG fluorescence angiography led to a change in surgical management in 80% of the patients. A follow up study by the same group showed a decrease in pelviperineal non-healing in the ICG group compared to the control group (22% vs 42%; p ¼ 0.051) [95]. However non-significant, this study showed a trend towards improved outcomes after ICG fluorescence angiography guided omentoplasty.…”
Section: Omentoplastic Perfusionmentioning
confidence: 47%
“…Remarkably, ICG fluorescence angiography led to a change in surgical management in 80% of the patients. A follow up study by the same group showed a decrease in pelviperineal non-healing in the ICG group compared to the control group (22% vs 42%; p ¼ 0.051) [95]. However non-significant, this study showed a trend towards improved outcomes after ICG fluorescence angiography guided omentoplasty.…”
Section: Omentoplastic Perfusionmentioning
confidence: 47%
“…First, the mobilization of the greater omentum might jeopardize its vascularization, leaving a (partially) devascularized omentum in the neo-pelvis. 19,20 A partially devascularized, necrotic omentum could be a source of infection, balancing out the potential benefit of an omentoplasty. Finally, an imbalance regarding the extent of APR might have contributed to the higher pelviperineal complication rate after omentoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Slooter et al reported a pilot study for assessing omental perfusion during omentoplasty in salvage surgery for pelvic sepsis [ 21 ]. After establishing the feasibility of this technique, the same group went on to demonstrate the possible beneficial role in a subsequent cohort study [ 22 ]. They reported a much lower perineal non-healing rate in the group where ICG was utilized (22%) versus the controls (42%).…”
Section: Current Uses Of Icg In Colorectal Surgerymentioning
confidence: 99%